Rectangular Ring Antenna Excited by Circular Disc Monopole for WiMAX System - Souphanna Vongsack; Chuwong Phongcharoenpanich; Sompol Kosulvit; Kazuhiko Hamamoto; Toshio Wakabayashi (International Journal of Antennas and Propagation)
This research presents a rectangular ring antenna excited by a circular disc monopole (CDM) mounted in front of a square reflector. The proposed antenna is designed to cover a frequency range of 2.300–5.825 GHz and thereby is suitable for WiMAX applications. Multiple parametric studies were carried out using the CST Microwave Studio simulation program. A prototype antenna was fabricated and experimented. The measurements were taken and compared with the simulation results, which indicates good agreement between both results. The prototype antenna produces an impedance bandwidth (|S11| < −10 dB) that covers the WiMAX frequency range and a constant unidirectional radiation pattern (θ=0° and ∅=90°). The minimum and maximum gains are 3.7 and 8.7 dBi, respectively. The proposed antenna is of compact size and has good unidirectional radiation performance. Thus, it is very suitable for a multitude of WiMAX applications.